2021
DOI: 10.1101/2021.03.24.436479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncharted biosynthetic potential of the ocean microbiome

Abstract: Microbes are phylogenetically and metabolically diverse. Yet capturing this diversity, assigning functions to host organisms and exploring the biosynthetic potential in natural environments remains challenging. We reconstructed >25,000 draft genomes, including from >2,500 uncharacterized species, from globally-distributed ocean microbial communities, and combined them with ~10,000 genomes from cultivated and single cells. Mining this resource revealed ~40,000 putative biosynthetic gene clusters (BGCs), m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 141 publications
0
20
0
Order By: Relevance
“…All raw sequences can be accessed through the NCBI at BioProject PRJEB43305, and the code for all the analyses were detailed in submitted publication by Paoli et al . 60 .…”
Section: Methodsmentioning
confidence: 99%
“…All raw sequences can be accessed through the NCBI at BioProject PRJEB43305, and the code for all the analyses were detailed in submitted publication by Paoli et al . 60 .…”
Section: Methodsmentioning
confidence: 99%
“…To enable marine bioprospecting, several studies have published meta-omics data resources [239][240][241][242] including the Tara Oceans sampling expeditions which sequenced over 600 metatranscriptomes and 1000 metagenomes from >200 globallydistributed sampling stations. 23 The combination of Tara Oceans data with Global Ocean Sampling, 10 Malaspina, 241 and bioGEOTRACES expeditions 240 enabled the assembly of the largest genome-resolved ocean resource to date.…”
Section: Global Ocean Microbiomicsmentioning
confidence: 99%
“…Previous analysis in our lab also found that reference genomes from cultivated marine isolates rarely overlapped with marine SAGs or MAGs, indicating that multipronged approaches of cultivation and multiple types of sequencing contributes to a greater genome-resolved understanding of ecological community composition. 242 There are still relatively few cases of biosynthetic enzyme discovery from SAGs. As the earliest example applied to natural product studies, Grindberg et al detected the cyanobacterial apratoxin biosynthetic pathway in a mixed bacterial assemblage through a combination of single-cell sequencing, in silico mining, and a metagenomic fosmid library screening.…”
Section: Single-cell Genomicsmentioning
confidence: 99%
See 2 more Smart Citations